2012
DOI: 10.1515/jbcpp-2011-0034
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective and in vivo antioxidant activities of ethanolic extract of whole fruit of Lagenaria breviflora

Abstract: The present study suggested that treatment with LB extract enhances the recovery from CCL4 induced hepatic damage and oxidative stress via its antioxidant and hepatoprotective properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…CCl 4 proved to be highly useful as an experimental model for the study of liver damage in humans 33 34 35 . It is usually used through intraperitoneal injection or oral administration, and with a dosage of 0.2 to 5 ml/kg liver fibrosis is achieved between 4 and 18 weeks 36 37 . In this study, the mild, medium and severe liver fibrosis rat models were developed through differential doses (25–62.5%) and exposure duration (10–15 weeks) of CCl 4 .…”
Section: Discussionmentioning
confidence: 99%
“…CCl 4 proved to be highly useful as an experimental model for the study of liver damage in humans 33 34 35 . It is usually used through intraperitoneal injection or oral administration, and with a dosage of 0.2 to 5 ml/kg liver fibrosis is achieved between 4 and 18 weeks 36 37 . In this study, the mild, medium and severe liver fibrosis rat models were developed through differential doses (25–62.5%) and exposure duration (10–15 weeks) of CCl 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, APAP overdose depletes glutathione levels and generates free radicals (Jaeschke and Bajt, 2006). Potent antioxidants and several medicinal plants extracts already used to treat liver diseases prevent APAP induced hepatotoxicity (Fahim et al, 1999;Sotelo-Felix et al, 2002a), which have also been used in the treatment of liver diseases Saba et al, 2012;Singhal and Gupta., 2012;Liu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…25 Heavy metals have hepatotoxic potential due to production of oxidative stress to the tissue, lagenaria siceraria has remarkable oxidative capability and is in a position to reverse the oxidative stress and concomitantly can minimize the inflammation in the interstitium and area of portal triads. 26,27 Lagenaria siceraria on biochemical evaluation was found to have flavonoids. Plants which have flavonoids have an impact on arachidonic acid metabolism and are thought to have antiinflammatory, cardio protective and anti-allergic effects 28,29 Present study also revealed that when lagenaria siceraria was simultaneously given to the animals who were exposed to heavy metal toxicity the process of inflammation and fibrosis was reverted (Table-I&II).…”
Section: Discussionmentioning
confidence: 96%